Efecto de varias dosis de giberelinas en la germinación de diferentes ecotipos de chirimoya en Loja - Góngora Cordero, Danny Icel (2024)
The cherimoya (Annona cherimola Mill.) is a fruit highly valued for its nutritional, digestive, and medicinal properties, with high demand in both domestic and international markets. However, the propagation of this species is hindered by the low and slow germination rate of its seeds due to dormancy. The aim of this study was to determine the effect of different concentrations of gibberellins on the germination of different cherimoya ecotypes (lisa, impressa, and mamillata) in Loja, Ecuador. Seeds from each ecotype were collected, subjected to mechanical scarification, and treated with gibberellic acid at concentrations of 0 ppm, 3500 ppm, 5000 ppm, and 6500 ppm. Germination percentage and initial plant growth (height, stem diameter, and number of leaves) were then evaluated. The results showed that mamillata ecotype seeds treated with 3500 ppm and 6500 ppm of gibberellins achieved the highest germination percentages, reaching 63% by the end of the trial (day 123). However, no significant differences were found in the initial growth of the plants, regardless of the gibberellin concentration applied or the ecotype studied. This study suggests that gibberellins can significantly improve the germination of cherimoya seeds in certain ecotypes, particularly in the case of mamillata, but their impact on early plant development is limited. These results provide valuable information for future cherimoya propagation and breeding programs, focusing on strategies to overcome seed dormancy and optimize cultivation techniques in the early stages of development.